Hydrographic Training and Technical Assistance to Developing Countries - Norwegian Assistance to Mozambique - Saether, Tor (The International Hydrographic Review, 2015)
Norway has, through the Norwegian Agency for Development Assistance (NORAD), actively supported the Hydrographic organization of the Mozambique government since 1986. At the beginning, the Norwegian Hydrographic Service (NSKV) was brought in, as a consultant, for the first two years, with its own staff in Mozambique, then later, as a backup for a NORAD employed hydrographic surveyor. A new contract, effective from 1st January 1991, has been signed, this time between the Mozambican Organization, which is now called Instituto Nacional de Hidrografia e Navegaçâo (INAHINA) and NSKV. It is funded by NORAD, and NSKV has undertaken to build and develop INAHINA to such an extent that it will be able to continue operations and continue to perform satisfactorily after the withdrawal of NSKV-assistance.